Research culture among academics at higher education institutions: a case study at the International Islamic University Malaysia - Mohin, Mohaida; Mamat, Arifin; Ismail, Nik Ahmad Hisham (2017)
Academic research has been converted into a basic element of the mission of universities, through which they contribute to the success of regional, economic, cultural and educational development plans. Thus, the success of a university today is likely being measured through the number of research, publications and intellectual properties produced by academic staff. Therefore, this study attempts to investigate the existence of research culture at the International Islamic University of Malaysia (IIUM) and examines academic staff perceptions toward it. It employed a survey method to gather the data. A survey was administered to a sample of academic staff at all Kulliyyahs (Faculties), Institutes and Centers at IIUM. A number of 411 academic staff participated as respondents in this study. A set of questionnaire consisting of 39 items was constructed to examine the research culture at IIUM. Where as a simple descriptive statistical analysis which includes percentages, frequencies and means was used for data analysis. The outcomes of this research are that tangible practical implications have emerged from the data analysis and the discussions. It is evident that academics are prepared to practice the research culture at IIUM, as well as their dispositions to engage in intellectual discourse. The academic staff are aware of the importance of research, the procedure of conducting research and that they believe that by doing research, their teaching competencies can be further improved